PO202 Natural history study in hereditary sensory neuropathy type 1. (1st December 2017) - Kugathasan, Umayial; Laura, Matilde; Evans, Matthew; Morrow, Jasper; Thornton, John; Hornemann, Thorsten; Phadke, Rahul; Lauria, Giuseppe; Blake, Julian; Reilly, Mary M
Abstract : HSN1 secondary to SPTLC1/2 mutations is a rare, slowly progressive neuropathy leading to profound sensory loss and variable motor deficit. It is associated with accumulation of 1-deoxysphingolipids (1-dSL) which have been shown to be neurotoxic. l-serine is a candidate therapy for HSN1. The lack of outcome measures is a critical limiting factor for undertaking clinical trials. We undertook a one year natural history study to identify responsive outcome measures to be used in a future l-serine trial. A variety of assessments were performed and included: CMT Neuropathy score (CMTNS), muscle MRI, computerised myometry, quantitative sensory testing (QST), neurophysiological assessment, skin biopsy for intra-epidermal nerve fibre density (IENFD), 1-dSL plasma levels and pain questionnaires. Standardised Response Mean (SRM) was used to compare responsiveness between tests. 35 patients were recruited: 31 with SPTLC1 (C133W) and 4 with SPTLC2 mutations. There was marked heterogeneity in the severity of the phenotype with males being more severely affected. The majority of the assessments showed small/very small responsiveness (SRM <0.5). In contrast MRI of the calf showed excellent responsiveness (SRM=2.2) over 12 months, so that it could be used as responsive outcome measure in a placebo controlled trial with 15 patients in each arm.